Audit on Going Concern in the Context of an Institutional Approach - L. S. Makhanko (Учёт. Анализ. Аудит, 2023)
In the conditions of uncertainty, going concern auditing (GCA) or auditing of continuity of operations is an effective tool for preventing adverse effects and consequences of disruption of the stable functioning of the organization and at the same time a possible situation of systemic defaults and non-payments associated with the retirement or disposal of one of the counterparties in the payment and settlement chain. The aim of this article is to substantiate the nature and examine the issues of the degree of implementation into practice and the completeness of disclosure of all the functions of going concern auditing, depending on the characteristics of the national economy and the institutional environment. The research is based on a dichotomous approach, in which two types of institutional matrix are distinguished: the Xmatrix and the Y-matrix. At the same time, all the participants in the auditing process are divided into three groups: the audited person or entity, the auditor (auditing organization or individual entrepreneur/sole proprietor), the regulators of auditing activities. Various scenarios of their behavior depending on the institutional matrix are described in this article. The purpose of the study is to develop the theoretical foundations of going concern auditing in the context of ensuring that its functional capabilities meet and comply with the established conditions and traditions of the host institutional environment. The study was carried out on the example of the Republic of Belarus. The research used scientific methods of theoretical (analysis and synthesis, grouping, generalization, systematization) and empirical (selective observation, comparison, case study) levels. The significance of the conducted research is in clarifying the methodological foundations of the going concern auditing based on the institutional approach, which made it possible to take into account and explain the impact on the current practice of the features of a specific institutional model and develop practical recommendations regarding the completeness of the functional capabilities of the business on going audit in relation to the features of the national economic system.